Analysis of Factors that Affect the Determination of the Rental Value of the Placement of an Automated Teller Machine in Medan City - Sembiring, Erwandi Martinus; Siahaan, Elisabet; Gultom, Parapat (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
A prevailing phenomenon indicates that government appraisers at the State Asset and Auction Service Office (KPKNL) in Medan still employ conventional methods for the rental valuation of Automated Teller Machine (ATM) placements. This practice contradicts the Decree of the Director General of State Assets Number 547/KN/2022, which mandates the use of the Valuation Component and Survey List (DKPS) model through a desktop valuation approach. Addressing this discrepancy, this study aims to analyze the factors that influence the determination of ATM placement rental values in Medan City, thereby providing a basis for the development of a more objective valuation model.This research utilizes a quantitative approach with multiple regression analysis to identify the influence of variables such as distance to the Central Business District (CBD), transaction year, leased object type, ATM space type, lease period, accessibility, and area designation. The findings reveal that distance to the CBD has a significant negative effect on rental value. Conversely, transaction year, the type of leased object, space type, lease period, and designation as a shopping center or public service area exhibit a positive and significant influence. While accessibility and road type showed a positive correlation, their effects were not statistically significant. The resulting regression model achieved an R-squared value of 96.37%, demonstrating its excellent capability in explaining the variance in rental values.These findings provide a robust empirical foundation for government appraisers to transition to the regulated desktop valuation method. Moreover, the results offer critical insights for ATM owners in optimizing location selection. This study recommends that the significant factors identified be integrated into the DKPS model to enhance the accuracy, efficiency, and consistency of ATM rental valuations at KPKNL Medan, ultimately supporting the financial performance of asset owners.